2019
DOI: 10.1101/2019.12.19.882795
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampus and amygdala fear memory engrams re-emerge after contextual fear relapse

Abstract: 14 The formation and extinction of fear memories represent two forms of learning that each 15 engage the hippocampus and amygdala. How cell populations in these areas contribute to fear 16 relapse, however, remains unclear. Here, we demonstrate that, in mice, cells active during fear 17 conditioning in the dentate gyrus of hippocampus and basolateral amygdala exhibit decreased 18 activity during extinction and are re-engaged after fear reinstatement. In vivo calcium imaging 19 reveals that reinstatement drives… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…All mice were previously used in a fear conditioning and extinction study between four and ten months of age (Zaki et al, 2021;Orlin et al, in preparation). They were allowed to rest undisturbed in their home cage for a minimum of one week, and then handled for an additional week for 10-15min/day before being trained for this study.…”
Section: Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…All mice were previously used in a fear conditioning and extinction study between four and ten months of age (Zaki et al, 2021;Orlin et al, in preparation). They were allowed to rest undisturbed in their home cage for a minimum of one week, and then handled for an additional week for 10-15min/day before being trained for this study.…”
Section: Behaviormentioning
confidence: 99%
“…Fear conditioning and extinction studies also compare similar outward patterns of behavior before conditioning and after extinction, but it is possible the prior threat association of the environment constitutes a more fundamental change to the memory of that environment than does a different pattern of turn responses; outcomes with different valence relate to different survival instincts, which may engage fundamentally different memory processes (Chen et al, 2020). Even if animals do not display signs of threat expectation after extinction, the condition of the environment is changed in that safety is demonstrably not guaranteed (Zaki et al, 2021). The tasks used in our study may also engage different constellations of neural circuits, as previous work suggests that egocentric, body-turn responses (Turn Right) are supported by striatal circuits while allocentric responses (Go East) are supported by the hippocampus (Chang & Gold, 2003;McDonald & White, 1994;Mcintyre et al, 2003;Packard & McGaugh, 1996), although other studies have proposed that both tasks may be represented as arm-arm location associations in over-trained animals (Futter & Aggleton, 2006).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In general, new experiences do not entirely destabilize previously existing hippocampal representations (Cheng & Frank, 2008;Wilson & McNaughton, 1993). Additionally, in familiar environments, a small proportion of place cells can remap their activity to encode new paths (Alvernhe et al, 2011;Lever et al, 2002), reward locations (Boccara et al, 2019;Butler et al, 2019;McKenzie et al, 2013), and fear/threat responses (Moita et al, 2004;Moita et al, 2003;Wang et al, 2012;Zaki et al, 2021). However, in many instances these paradigms do not reinstate a prior behavioral contingency, so in these cases it is challenging to assess whether observed remapping is attributable to representing the new environmental features and behavioral demands, or if it is the result of permanently modifying the previously existing memory representation to reduce interference with new learning.…”
Section: Introductionmentioning
confidence: 99%
“…We often refer to these ensembles, active during memory encoding, as memory traces or engrams 16,17 and these engrams are reactivated during retrieval 14,18 . Findings from several studies have shown that specific memories, including fear memories, can be disrupted by inhibition of associated engrams 12,[19][20][21][22][23] . Specifically, the dorsal dentate gyrus (dDG) of the hippocampus is important for encoding contextual memories 24,25 , and has been implicated in the pathophysiology of a number of anxiety disorders 25,26 .…”
Section: Introductionmentioning
confidence: 99%